2006
DOI: 10.1261/rna.2266506
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the glmS ribozyme suggest only structural roles for divalent metal ions

Abstract: The glmS ribozyme is a riboswitch class that occurs in certain Gram-positive bacteria, where it resides within mRNAs encoding glucosamine 6-phosphate synthase. Members of this self-cleaving ribozyme class rapidly catalyze RNA transesterification upon binding GlcN6P, and genetic evidence suggests that this cleavage event is important for down-regulating GlmS protein expression. In this report, we present a refined secondary structure model of the glmS ribozyme and determine the importance of a conserved pseudok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
151
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(164 citation statements)
references
References 63 publications
12
151
1
Order By: Relevance
“…Early truncation analysis showed that the nucleotides downstream of C75 are nonessential for catalytic activity of the B. subtilis ribozyme , although recent kinetic analyses indicate that a pseudoknot in this region enhances self-cleavage activity by stabilizing the core structure at limiting Mg 2+ concentrations (Wilkinson and Been 2005;Roth et al 2006). For our studies, in which we were particularly interested in the structural impact of ligand binding on the catalytic core, we therefore focused on the structurally presumably more labile catalytic core of the riboswitch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early truncation analysis showed that the nucleotides downstream of C75 are nonessential for catalytic activity of the B. subtilis ribozyme , although recent kinetic analyses indicate that a pseudoknot in this region enhances self-cleavage activity by stabilizing the core structure at limiting Mg 2+ concentrations (Wilkinson and Been 2005;Roth et al 2006). For our studies, in which we were particularly interested in the structural impact of ligand binding on the catalytic core, we therefore focused on the structurally presumably more labile catalytic core of the riboswitch.…”
Section: Resultsmentioning
confidence: 99%
“…Data were fit with a single-exponential increase function to yield the reported rate constant k obs . activity of our G1 construct or primarily plays a structural role, as recently suggested for the cis-acting ribozyme (Klein and Ferre-D'Amare 2006;Roth et al 2006). Therefore, we measured cleavage activity under buffer conditions of 50 mM HEPES-KOH (pH 7.5), 200 mM KCl, 2 mM EDTA, and 1 mM Co(NH 3 ) 6 3+ in the presence of 10 mM GlcN6P at 25°C.…”
mentioning
confidence: 94%
“…In certain Gram-positive bacteria, glmS ribozymes repress the production of GlmS protein by monitoring the concentration of its key enzymatic product, GlcN6P. Previously known examples of glmS ribozymes were identified by using comparative sequence analysis algorithms and were exclusively found in Grampositive bacteria (Barrick et al 2004;Winkler et al 2004;Roth et al 2006;Gardner et al 2009). Each bacterium that contains a glmS ribozyme carries a single representative exclusively located in the 59 UTR of its glmS gene.…”
Section: Introductionmentioning
confidence: 99%
“…À5 min À1 to >10 min À1 under physiological conditions upon binding of GlcN6P (McCarthy et al 2005;Roth et al 2006;Klein et al 2007a). On the other hand, glucose-6-phosphate (Glc6P), which has a hydroxyl group instead of an amine group, does not activate self-cleavage of glmS and acts as an inhibitor (McCarthy et al 2005).…”
Section: Introductionmentioning
confidence: 99%